Lower Campanian palynoflora from the Araçatuba Formation (Bauru Group), Southeastern Brazil - Arai, Mitsuru [UNESP]; Fernandes, Luiz Alberto (Elsevier, 2023)
This paper presents the first record of a rich palynoflora within the Bauru Group (Cretaceous of southeastern Brazil). The Bauru Group is rich in animal fossils, but has been virtually barren in palynomorphs. There are only two previous palynological works from the Bauru Group: (1) that of the São Carlos Formation, whose outcrop is located outside the formal boundary of the Bauru Basin, and (2) the extremely poor and poorly preserved palynoflora from a coprolite of the Marília Formation. The material studied here, from the Araçatuba Formation, is the only one palyniferous sample from a groundwater well drilled in the central-west region of the state of São Paulo. The Araçatuba Formation, constituted by swamp deposits, rests directly on the basalts of the Serra Geral Group. The Araçatuba palynoflora contains index palynomorphs – Cretacaeiporites polygonalis, C. scabratus and Hexaporotricolpites emelianovi – signifying an early Campanian age. Moreover, the absence of Santonian indices and of older ages, confirms attribution to the lower Campanian. In paleoclimatic terms, the assemblage suggests aridity, given the abundance of ephedroid pollen grains and the low frequency of pteridophytic spores. The occurrence of spores of water ferns confirms the paludal setting. The aqueous environment is also suggested by the occurrence of zooclasts derived from crustacean eggs. However, the virtual absence of phytoplankton may indicate the ephemeral nature of the water body.
Keywords: Brazil; Cretaceous; Paleoclimatology; Palynology; Palynostratigraphy